ENHANCING SPIRITUAL CARE IN NURSING PRACTICE: EXPLORING THE RELATIONSHIP BETWEEN IMPLEMENTATION OF SPIRITUAL ASPECTS AND FULFILLMENT OF PATIENTS' SPIRITUAL NEEDS - Aris Citra Wisuda, Aris Citra Wisuda; Tukimin bin Sansuwito; Citra Suraya; Dian Emiliasari (Journal Of Nursing Science Research, 2024)
Background: Nurses are integral to comprehensive patient care, addressing biological, psychological, social, and spiritual dimensions. Spiritual care is a crucial component of nursing, ensuring patients' holistic well-being. Objective: This study explores the link between nurses' spiritual application and inpatients' spiritual fulfillment. Method: Conducted at Siti Khadijah Islamic Hospital, Palembang from October to December 2023, this quantitative research sampled 42 inpatients through simple random sampling. Data collected via questionnaires were analyzed using univariate and bivariate methods (chi-square). Instruments included "Aspects of Application of Spirituality" and the Spiritual Care Competency Scale (SCCS), alongside the Spiritual Needs Questionnaire (SpNQ) for assessing spiritual fulfillment. Results: the relationship between the application of the spirituality aspect of nurses and the fulfillment of the spiritual needs of inpatients is 64.3%, indicating that the application of the spirituality aspect of nurses is considered not good. Meanwhile, as many as 35.7% of patients indicated that the implementation of the spirituality aspects of nurses was good. Chi-square analysis (p=0.011) indicated a significant correlation between nurses' spiritual practices and inpatients' spiritual fulfillment. Recommendation: Enhancing spiritual practices requires structured interventions like spiritual skills training, framework development, monitoring systems, leadership support, and collaborative training. These measures aim to elevate healthcare service quality and ensure holistic patient care.